2020
DOI: 10.1002/ese3.641
|View full text |Cite
|
Sign up to set email alerts
|

Geological characteristics and abnormal pore pressure prediction in shale oil formations of the Dongying depression, China

Abstract: Pore pressures in shale oil formations in the Dongying depression of the Bohai BayBasin are highly overpressured. Understanding overpressure principles not only can reveal the mechanism of shale oil generation to provide prospects for shale oil exploration and production, but also can reduce potential drilling risks and provide insights for sweet spot identification. Overpressure generation mechanisms are analyzed based on petrophysical data, core analysis, sedimentation rate, oil saturation, and smectite and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In the evaluation process of shale oil production capacity, understanding the extent of influence and interrelationships among various factors is crucial [16]. However, within these factors, inevitable correlations or overlaps among certain parameters may affect the final evaluation outcomes.…”
Section: Corresponding Loss Function Y Leftmentioning
confidence: 99%
“…In the evaluation process of shale oil production capacity, understanding the extent of influence and interrelationships among various factors is crucial [16]. However, within these factors, inevitable correlations or overlaps among certain parameters may affect the final evaluation outcomes.…”
Section: Corresponding Loss Function Y Leftmentioning
confidence: 99%
“…Previous studies have suggested that the overpressure generated by different mechanisms should be predicted in different methods [24]. The overpressure in the Dongying Depression is mainly caused by oil generation from the source rocks [1,25], while compaction disequilibrium may have contributed to the overpressure in the north Steep Slope zone of the Dongying Depression [26,27]. Thus, the pore pressure can be calculated by the Eaton Formula [28,29]:…”
Section: Excess Pressure Prediction Using Well Log Datamentioning
confidence: 99%
“…Reservoir characteristics of the sandstone such as geometry, mineralogical composition, pore characteristics, porosity, permeability, textural framework, and maturity are evaluated by depositional settings of the sandstones, whereas the diagenesis may affect the reservoir porosity by post-depositional processes (Bjørlykke 2014;Cantarero et al 2020;Mangi et al 2020). Reservoir quality is the main factor controlling the prospectivity during the exploration and production of hydrocarbon (Zhang et al 2020). Lower Goru sandstone reservoirs in the Lower Indus basin have been studied with the help of core cuttings of well KD-01 well from the sandstone intervals.…”
Section: Introductionmentioning
confidence: 99%